AVC isquêmico na infância associado à COVID - 19 - Victor Hugo Alves Diniz; Guilherme Barros de Mattos; Lucas Roncoletta Vicentino; Vinicius Camargo Achermann; Maria Clara Pimenta Figueiredo; Gustavo Manginelli Lamas; Flavia Faganello Colombo; Katia Maria Ribeiro Silva Schmutzler; Elizete Aparecida Lomazi (Residência Pediátrica)
This case report deals with an ischemic stroke in a 2-year-and-5-month-old child associated with COVID-19. The patient, initially presenting with paresis and facial paralysis, tested positive for the coronavirus. Additional examinations suggest an acute vascular event without apparent risk factors. The discussion highlights the potential relationship between COVID-19 and pediatric ischemic stroke. The case aims to contribute to the understanding of the possible link between COVID-19 and stroke in children, addressing diagnosis, treatment, and potential underlying mechanisms of this association.